2006
DOI: 10.1073/pnas.0603900103
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt tropical climate change: Past and present

Abstract: Three lines of evidence for abrupt tropical climate change, both past and present, are presented. First, annually and decadally averaged ␦ 18 O and net mass-balance histories for the last 400 and 2,000 yr, respectively, demonstrate that the current warming at high elevations in the mid-to low latitudes is unprecedented for at least the last 2 millennia. Second, the continuing retreat of most mid-to low-latitude glaciers, many having persisted for thousands of years, signals a recent and abrupt change in the Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
303
2
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 425 publications
(335 citation statements)
references
References 50 publications
18
303
2
12
Order By: Relevance
“…The remaining glaciers throughout Africa (14-16) will soon disappear, most glaciers in tropical South America are in rapid retreat (12,(17)(18)(19), the few remaining glaciers in Indonesia are rapidly disappearing (20), and on balance most Tibetan glaciers, including many in the Himalayas, are also retreating (21). Moreover, some of the highest glaciers in the Himalayas are now wasting from the surface downward (22) just like the ice fields on Kilimanjaro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining glaciers throughout Africa (14-16) will soon disappear, most glaciers in tropical South America are in rapid retreat (12,(17)(18)(19), the few remaining glaciers in Indonesia are rapidly disappearing (20), and on balance most Tibetan glaciers, including many in the Himalayas, are also retreating (21). Moreover, some of the highest glaciers in the Himalayas are now wasting from the surface downward (22) just like the ice fields on Kilimanjaro.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the relative importance of the multiple drivers responsible for the loss of Kilimanjaro's summit ice fields, these shrinking ice fields are not unique (12,13). The remaining glaciers throughout Africa (14-16) will soon disappear, most glaciers in tropical South America are in rapid retreat (12,(17)(18)(19), the few remaining glaciers in Indonesia are rapidly disappearing (20), and on balance most Tibetan glaciers, including many in the Himalayas, are also retreating (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although these series were derived from different proxies, such as tree rings, historical documents, stalagmites, ice cores, and lake sediments, they provide quantitative estimates of past temperatures. As seen in Table 1, nine of the series represent annual temperatures [8,19,20,22,23], while the others represent seasonal temperatures [9-18, 21, 24]. In addition, our previous study [25] demonstrated that the proxies of seasonal temperatures can explain 44%-90% of the variability of annual temperature within the instrumental calibration period ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…In China, much effort has been spent in the last few decades to reconstruct regional proxy temperature series with lengths of 500-2000 years from historical documents [8][9][10][11][12][13][14][15], tree rings [16,17], stalagmites [18], ice cores [19], and lake sediments [20][21][22][23][24]. Uncertainty analysis of these regional reconstructions indicates that warming during the 10-14th centuries in some regions might be comparable in magnitude to the warming of the last few decades of the 20th century that was unprecedented in the past 500 years [25].…”
mentioning
confidence: 99%
“…Other sites recognizing this included Wright's mapped Taptapa moraine at 10.1 ka (Wright, 1984), followed by rapid deglaciation. The Quelccaya Ice Cap was recognized to be at the limit by 10 ka, given peat exposed at the margin (Thompson et al, 2006;Buffen et al, 2009). …”
Section: Discussion: Synthesis Of Dates and Climate Eventsmentioning
confidence: 99%